Luther's legacy: salvation and English reformers, 1525-1556 - Trueman, Carl R. (Clarendon, 1994)
A study of the Christian idea of salvation as seen through the eyes of five 16th-century English reformers, John Frith, John Hooper, Robert Barnes, John Bradford, and the Bible translator William Tyndale. The author sets their views in context, both historically and intellectually.